KETENAGAAN DI TAMAN BACAAN MASYARAKAT - B. P. Sitepu (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Reading skill and reading habit should be developed in all levels of society in establishing reading and learning society which can not be avoided in this modern age. The Community Reading Centers (CRC) which have been developed since nineteen fifties are expected to stimulate the establishment and the development of reading societies all over Indonesia. The Government has provided some grants and facilities to empower the Centers to activate their functions. As the expectation for these centers is so great, this preliminary study made a close observation on four Centers located in Medan, North Sumatra. Attention was focused on the number and quality of man power serving the attendants in each Center. It is believed, the manpower plays a significant role in the operation of the Center to do its function to reach the predetermined goals. This preliminary study finds out that the quality of the manpower in the four Centers influence the quality and quantity of the services provided. The Center with experienced and active personnel is able to complete its function better than the ones with lack of experiences and initiatives. This study suggests the Government to give priority to training program in empowering the Centers.